Diagnostic performance of serum 14-3-3η protein versus conventional serological markers in early rheumatoid arthritis - Liu, Tiantian; Guo, Wenbin (Frontiers in Immunology, 2026)
ObjectiveConventional biomarkers for rheumatoid arthritis (RA) only have a ~70% sensitivity, making early diagnosis difficult. With its high concentration in synovial fluid, the 14-3-3η protein is a promising new biomarker for the early identification of RA in Chinese people.MethodsIn this case-control study, 90 disease controls, 110 healthy controls, 72 established RA patients, and 56 early RA patients were enrolled. The 14-3-3η protein’s diagnostic performance was evaluated utilizing ROC curve analysis in comparison to anti-CCP antibodies, RF, CRP, IgM, and ESR. To control for confounding variables, multivariable logistic regression models that were adjusted for sex and age were used.Results14-3-3η showed exceptional diagnostic performance, with AUC ≥0.85 for both early and developed RA. In early RA, anti-CCP demonstrated better specificity (96.4%) and a positive likelihood ratio (21.2%), while 14-3-3η had the highest sensitivity (88.1%) and the lowest negative likelihood ratio (0.14). There were no significant associations between 14-3-3η and traditional markers (P>0.05) according to Spearman correlation analysis.Conclusions14-3-3η protein serves as an independent and highly sensitive biomarker for early RA diagnosis, particularly valuable for ruling out disease. These biomarkers, combined with the high specificity of anti-CCP, provide supplementary diagnostic benefits for complete early RA assessment.